2021
DOI: 10.1101/2021.01.06.425548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution to alternative levels of stable diversity leaves areas of niche space unexplored

Abstract: One of the oldest and most persistent questions in ecology and evolution is whether natural communities tend to evolve toward saturation and maximal diversity. Robert MacArthur’s classical theory of niche packing and the theory of adaptive radiations both imply that populations will diversify and fully partition any available niche space. However, the saturation of natural populations is still very much an open area of debate and investigation. Additionally, recent evolutionary theory suggests the existence of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 57 publications
0
13
1
Order By: Relevance
“…As nicely summarized by Edwards et al . [2018], communities not at an ESS will experience selective pressure towards the ESS [however, see Doebeli & Ispolatov, 2014; Doebeli et al ., 2017; Rubin et al ., 2021, for discussions of non-equilibrium evolutionary dynamics]. In evolutionary time, super-saturated communities will likely experience the extinction of certain species and collapse to the ESS [e.g., 1].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As nicely summarized by Edwards et al . [2018], communities not at an ESS will experience selective pressure towards the ESS [however, see Doebeli & Ispolatov, 2014; Doebeli et al ., 2017; Rubin et al ., 2021, for discussions of non-equilibrium evolutionary dynamics]. In evolutionary time, super-saturated communities will likely experience the extinction of certain species and collapse to the ESS [e.g., 1].…”
Section: Resultsmentioning
confidence: 99%
“…Asymmetric competition can lead to both more interesting ecological (unstable or cyclic coexistence [Hernández-García et al ., 2009]) and evolutionary dynamics in high dimensional phenotype space (e.g., Red-Queen dynamics [Rubin et al ., 2021] or evolutionary chaos [Doebeli et al ., 2017]), depending on the specific functional form of the competition kernel. While diversity patterns due to asymmetric competition is beyond the scope of this article, while investigating systems with non-stable (Red Queen) evolutionary dynamics we found that randomly assembling super-diverse communities was possible, but exceedingly rare [Rubin et al ., 2021], creating a possible analogy to the difficulties in creating saturated communities with symmetric competition. We have also described a related phenomenon where continual selection can trap communities in low diversity meta-stable states [Rubin et al ., 2021].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations